Respuesta :

Answer:

Step-by-step explanation:

x1  

= −0 − √ 02 − 4×16×9  

2×16

= 0 − 24 × √ 1 i  

32

= −0.75i

x2  

= −0 + √ 02 − 4×16×9  

2×16

= 0 + 24 × √ 1 i  

32

= 0.75i

Answer: +3/4 i and - 3/4 i

Step-by-step explanation:

16x^2 + 9 = 0

subtract 9 from bothside

16x^2 + 9 - 9 = 0 - 9

16x^2 = -9

Divide bothside by 16

16x^2 / 16 = - 9/16

x^2 = - 9/16

take the square root of bothside

x = √ -9/16

x = √ 9/16 × √-1

x = ± 3 / 4 i

Note : √ -1 = i

Therefore; x = 3i/4 and - 3i/4 i

Otras preguntas